The influence of the shift work system on dietary factors contributing to the development of cardiovascular diseases (Journal of Medical Science, 2019)
Aim. The aim of this study was to assess eating behavior in the groups of women who are working on different, unchanged shifts as well as identifying differences in the consumption of nutrients that may increase the risk of cardiovascular disease. Material and Methods. The study was carried out among 300 randomly selected women working in a permanent shift (morning, afternoon, night). In the study, the assessment of the daily intake was carried out using 24-h dietary recall. Anthropometric measurements were carried out to assess the nutritional status. The interview regarding the food consumption was complemented by dietary questionnaire about selected lifestyle parameters contributing to the development of cardiovascular disease and the type of their work. Results. The body mass index (BMI) in all groups was within the adequate values. The analysis of waist to hip ratio (WHR) showed that in the morning and night shift, was exceeded the adequate values recommended in the prevention of cardiovascular disease (WHR = 0.83 ± 0.1 in both groups). The analysis of the daily food rations of women revealed disparities regarding nutritional recommendations. Statistically significant differences in protein and saccharose intake were observed (p > 0.05). The average vitamin D content in the daily food rations of women was insufficient (average 1.4 µg per day); however, it was not statistically significant. Conclusions. The shift work system was influence on eating behaviors in study women. In particular in women which were worked on the night shift, which may contribute to the development of cardiovascular disease in the future.